Do Change Management Influence ERP Implementation Success? Evidence from Morocco - Mahjoubi, Smail; Kabbaj, Smail (International Review of Management and Marketing, 2025)
This study investigates the change management in the implementation of Enterprise Resource Planning (ERP) systems within Moroccan companies. Focusing on a range of technological, organizational, and environmental (TOE) elements, this research aims to identify key drivers and challenges that companies face in digital transformation. Through an analysis of various case studies and empirical data, the study evaluates the roles of managerial support, employee engagement, infrastructure alignment, and proactive risk management in ensuring ERP project success. Findings highlight the necessity of a robust change management framework, aligned strategic goals, and sufficient resource allocation for achieving sustainable ERP implementation success. This research contributes to the existing literature by offering a comprehensive model for ERP system adoption in Moroccan companies, providing practical insights for organizations seeking to enhance their competitive edge in a digitalized market.